2013
DOI: 10.7150/ijms.6389
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Coronary and Carotid Atherosclerosis in Patients with Severe Degenerative Aortic Stenosis

Abstract: Background. Patients with degenerative aortic stenosis (AS) exhibit elevated prevalence of coronary artery disease (CAD) and internal carotid artery stenosis (ICAS). Our aim was to investigate prevalence of significant CAD and ICAS in relation to demographic and cardiovascular risk profile among patients with severe degenerative AS.Methods. We studied 145 consecutive patients (77 men and 68 women) aged 49-91 years (median, 76) with severe degenerative AS who underwent coronary angiography and carotid ultrasono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
2
11
0
3
Order By: Relevance
“…1,2 Although considered a degenerative disorder typically affecting the elderly people, AS has gained importance in recent years because of population aging. 1–3 AS prevalence in subjects ≥65 years was estimated at 2% to 7%, with 5.5% of subjects >85 years diagnosed with AS 1–3 ; each year, ~22,000 deaths were attributed to valvular disease in the United States, with AS being particularly problematic because it carries a high mortality risk once symptoms have appeared. Furthermore, the multifactorial etiology of AS points to prominent roles played by traditional cardiovascular risk factors such as male gender, advanced age, smoking, hypertension, hypercholesterolemia, diabetes, metabolic syndrome, and atherosclerosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Although considered a degenerative disorder typically affecting the elderly people, AS has gained importance in recent years because of population aging. 1–3 AS prevalence in subjects ≥65 years was estimated at 2% to 7%, with 5.5% of subjects >85 years diagnosed with AS 1–3 ; each year, ~22,000 deaths were attributed to valvular disease in the United States, with AS being particularly problematic because it carries a high mortality risk once symptoms have appeared. Furthermore, the multifactorial etiology of AS points to prominent roles played by traditional cardiovascular risk factors such as male gender, advanced age, smoking, hypertension, hypercholesterolemia, diabetes, metabolic syndrome, and atherosclerosis.…”
mentioning
confidence: 99%
“…Furthermore, the multifactorial etiology of AS points to prominent roles played by traditional cardiovascular risk factors such as male gender, advanced age, smoking, hypertension, hypercholesterolemia, diabetes, metabolic syndrome, and atherosclerosis. 36 The equitable distribution of health care resources requires a better understanding of the epidemiology of AS, whereas identifying subgroups within the general population at high risk for AS. Previous research suggested that most AS-affected subjects (~70%) are >60 years, with a balanced gender ratio.…”
mentioning
confidence: 99%
“…При этом митральный стеноз при том же функциональном классе ХСН, что и АС, вносит меньший вклад в развитие ЭД и атеросклероза артерий, особенно коронарных. И хотя в литературе доказывается высокая степень взаимосвязи между каротидным, коронарным атеросклерозом и АС [5,6,8], механизм происходящих в клапане и в сосудистой стенке процессов различается. И если частота коронарного атеросклероза для обследованных с ХРБС (33,3 %) и АС О р и г и н а л ь н ы е и с с л е д о в а н и я (52,5 %) оказалась сопоставимой с описанной в литературе [7], то частота каротидного атеросклероза у пациентов с ХРБС (слева -72,3 %, справа -68,08 %) и АС (слева -93,2 %, справа -90,9 %) была значительно выше, чем по данным других исследований [5,6].…”
Section: Discussionunclassified
“…При этом пациенты с митральной и аортальной недостаточностью занимают «промежуточную» позицию с частотой коронарного атеросклероза от 41,9 до 44,4 % соответственно [7]. При этом в ряде работ отмечается снижение распространенности атеросклероза коронарных артерий у женщин старше 76 лет с выраженным АС [8]. Основное внимание в литературе уделено возможной взаимосвязи АС и атеросклероза коронарных артерий [9,10].…”
Section: Introductionunclassified
“…Вместе с тем в ряде работ отмечается снижение частоты атеросклероза коронарных артерий в группе женщин с аортальным стенозом старше 76 лет [9]. Однако основное внимание в литературе уделяется оценке взаимосвязи приобретенного аортального стеноза и атеросклероза коронарных артерий [10,11].…”
Section: Introductionunclassified